2011
DOI: 10.1590/s0100-83582011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de biótipos de Euphorbia heterophylla a doses de glyphosate

Abstract: A leiteira (Euphorbia heterophylla) é uma planta daninha de ciclo anual encontrada com frequência em lavouras de soja na região Sul do Brasil, controlada em lavouras de soja geneticamente modificada (Roundup Ready® - RR) com uso do herbicida glyphosate. Entretanto, nos últimos anos, o controle dessa espécie não tem sido satisfatório em alguns locais, provocando a suspeita de que foram selecionados biótipos resistentes ao herbicida. Diante disso, o objetivo deste trabalho foi avaliar, por meio de curvas de dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
3
15
0
1
Order By: Relevance
“…In glyphosate-tolerant biotypes of E. heterophylla, the dose of 720 g a.i. ha -1 was sufficient to cause plant death (Vargas et al, 2011).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In glyphosate-tolerant biotypes of E. heterophylla, the dose of 720 g a.i. ha -1 was sufficient to cause plant death (Vargas et al, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…The results of this study were similar to those observed by applying glyphosate at the same dose tested (2,160 g a.i. ha -1 ) on biotypes of Euphorbia heterophylla with suspected herbicide resistance, from RR ® soybean fields in the state of Rio Grande do Sul (Vargas et al 2011). For biotypes of Digitaria spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic characteristics between species can influence their response to herbicides (Vargas et al, 2011). The insensitivity of weeds to herbicides may result from the difficulty of absorption of the product, due to characteristics of the leaf blade, such as roughness, hairiness and chemical composition of the epicuticular wax (Sanchotene et al, 2008).…”
Section: Differencesmentioning
confidence: 99%
“…Studies in Brazil have shown resistance of the species to herbicides that inhibit acetolactate synthase (ALS) (VIDAL; MEROTTO JUNIOR., 1999) and protoporphyrinogen oxidase (PROTOX) (TREZZI et al, 2005) and that have a low level resistance to glyphosate (VARGAS et al, 2011). Herbicide resistance can interfere with the competitiveness of weeds (OLIVEIRA et al, 2014); therefore, this is an important issue for the maintenance of crop yields.…”
Section: Introductionmentioning
confidence: 99%